KNOCKDOWN WORK DESK: ENHANCING DESIGN STUDENT’S ACTIVITIES IN LIMITED SPACES - Akmal Nur Arifin; Andrianto Andrianto; Ica Ramawisari (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
With the increasing population, residential land is becoming more limited, including accommodations such as boarding houses, which are commonly used by students, including design students. Observation of design students at Telkom University revealed that the average size of boarding house rooms ranges from 9-12 m², equipped with facilities like wardrobes, bathrooms, and floor desks to support studying. However, these conditions pose challenges for design students due to their specific activities, such as sketching, using laptops or PCs, and creating mockups or models. The lack of supporting facilities in such limited spaces can hinder the productivity of design students. Furthermore, preliminary data shows that design students have a high level of mobility in terms of relocating residences, requiring an ergonomic work desk that can support their activities and mobility within limited space and access. Therefore, an ergonomic work desk with a knockdown system is needed to enhance flexibility and adaptability in constrained spaces and access, supporting the activities and mobility of design students. This research employs a qualitative approach with the User-Centered Design methodology. Data collection techniques include interviews, participant observation, questionnaires, documentation, and literature reviews. The study resulted in a work desk designed with ergonomic dimensions and a knockdown system to accommodate the specific activities of design students within limited space and mobility constraints.